Notices (Blackfriars, 1935)
Medieval Socialism. By Bede Jarrett, O.P., M.A. Catholic Reunion. An Anglican Plea by “Father Clement” The Story of the Relics of the Passion. H. M. Gillett. Things Temporal and Timeless. By J. P. Arendzen, D.D., Ph.D. the play gramophone: august releases gramophone: september releases